THE RELATIONSHIP BETWEEN MATERNAL AGE, PARITY, AND PREGNANCY ANEMIA WITH PERINATAL PROGNOSIS IN LOW BIRTH WEIGHT INFANTS - Leny; Rini Mayasari (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Perinatal prognosis in low birth weight (LBW) infants remains a major maternal and child health problem. Maternal factors such as maternal age, parity, and pregnancy anemia are suspected to be associated with adverse perinatal outcomes. To analyze the relationship between maternal age, parity, and pregnancy anemia with perinatal prognosis in LBW infants. This study used an observational analytic design with a case-control approach. A total of 250 respondents were included, consisting of case and control groups from Budi Mulia Medika Maternity Clinic Palembang. Data were analyzed using Chi-Square test and logistic regression analysis. The results showed a significant association between maternal age (p=0.001), parity (p=0.012), and pregnancy anemia (p<0.001) with perinatal prognosis in LBW infants. Multivariate analysis indicated that pregnancy anemia was the most dominant factor (OR=4.376; 95% CI: 1.893–10.108). Maternal age, parity, and pregnancy anemia are significantly associated with perinatal prognosis in LBW infants, with anemia being the most dominant factor.